An evaluation of Chrysomya chloropyga larvae meal as an iron and protein source when fed to broiler chickens - Van Aswegen, Mari (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.